Global generalized solvability in a strongly degenerate taxis-type parabolic system modeling migration–consumption interaction - Winkler, Michael (Zeitschrift für angewandte Mathematik und Physik)
Abstract The parabolic problem $$\begin{aligned} \left\{ \begin{array}{l} u_t=\Delta \big (u\phi (v)\big ), \\ v_t=\Delta v-uv, \end{array} \right. \end{aligned}$$ u t = Δ ( u ϕ ( v ) ) , v t = Δ v - u v , is considered in smoothly bounded subdomains of $${\mathbb {R}}^n$$ R n with arbitrary $$n\ge 1$$ n ≥ 1 . Under the assumptions that $$\phi \in C^0([0,\infty )) \cap C^3((0,\infty ))$$ ϕ ∈ C 0 ( [ 0 , ∞ ) ) ∩ C 3 ( ( 0 , ∞ ) ) is positive on $$(0,\infty )$$ ( 0 , ∞ ) and satisfies $$\begin{aligned} \liminf _{\xi \searrow 0} \frac{\phi (\xi )}{\xi ^\alpha }>0 \quad {\text{ and }} \quad \limsup _{\xi \searrow 0} \big \{ \xi ^\beta |\phi '(\xi )| \big \}<\infty \end{aligned}$$ lim inf ξ ↘ 0 ϕ ( ξ ) ξ α > 0 and lim sup ξ ↘ 0 { ξ β | ϕ ′ ( ξ ) | } < ∞ with some $$\alpha >0$$ α > 0 and $$\beta >0$$ β > 0 , for all reasonably regular initial data an associated no-flux type initial-boundary value problem is shown to admit a global solution in an appropriately generalized sense. This extends previously developed solution theories on problems of this form, which either concentrated on non-degenerate or weakly degenerate cases corresponding to the choices $$\alpha =0$$ α = 0 and $$\alpha \in (0,2)$$ α ∈ ( 0 , 2 ) , or were restricted to low-dimensional settings by requiring that $$n\le 2$$ n ≤ 2 .
Keywords: Applied Mathematics; General Physics and Astronomy; General Mathematics

Stabilization despite pervasive strong cross-degeneracies in a nonlinear diffusion model for migration–consumption interaction - Winkler, Michael (Nonlinearity)
Abstract A no-flux initial-boundary value problem for <?CDATA \begin{align*} \begin{cases} u_t = \Delta \big(u\phi(v)\big), \\[1mm] v_t = \Delta v-uv, \end{cases} \qquad \qquad (\star) \end{align*}?> <mml:mtable columnalign="right left right left right left right left right left right left" columnspacing="0.2777777777777778em 2em 0.2777777777777778em 2em 0.2777777777777778em 2em 0.2777777777777778em 2em 0.2777777777777778em 2em 0.2777777777777778em" rowspacing="3pt">ut=Δ(uϕ(v)),vt=Δv−uv,(⋆) is considered in smoothly bounded subdomains of <?CDATA $\mathbb{R}^n$?> Rn with <?CDATA $n\geqslant 1$?> n⩾1 and suitably regular initial data, where φ is assumed to reflect algebraic type cross-degeneracies by sharing essential features with <?CDATA $0\leqslant \xi\mapsto \xi^\alpha$?> 0⩽ξ↦ξα for some <?CDATA $\alpha\geqslant 1$?> α⩾1 . Based on the discovery of a gradient structure acting at regularity levels mild enough to be consistent with degeneracy-driven limitations of smoothness information, in this general setting it is shown that with some measurable limit profile <?CDATA $u_\infty$?> u∞ and some null set <?CDATA $N_\star\subset (0,\infty)$?> N⋆⊂(0,∞) , a corresponding global generalized solution, known to exist according to recent literature, satisfies <?CDATA \begin{align*} \rho(u(\cdot,t))\stackrel{\star}{\rightharpoonup} \rho(u_\infty) \quad \textrm{in } L^\infty(\Omega) \quad\;\; \textrm{ and } \quad\;\; v(\cdot,t)\to 0 \quad \textrm{in } L^p(\Omega)\; \textrm{for all } p\geqslant 1 \end{align*}?> <mml:mtable columnalign="right left right left right left right left right left right left" columnspacing="0.2777777777777778em 2em 0.2777777777777778em 2em 0.2777777777777778em 2em 0.2777777777777778em 2em 0.2777777777777778em 2em 0.2777777777777778em" rowspacing="3pt">ρ(u(⋅,t))⇀⋆ρ(u∞)in L∞(Ω) and v(⋅,t)→0in Lp(Ω)for all p⩾1 as <?CDATA $(0,\infty)\setminus N_\star \ni t\to \infty$?> (0,∞)∖N⋆∋t→∞ , where <?CDATA $\rho(\xi): = \frac{\xi^2}{(\xi+1)^2}$?> ρ(ξ):=ξ2(ξ+1)2 , <?CDATA $\xi\geqslant 0$?> ξ⩾0 . In the particular case when either <?CDATA $n\leqslant 2$?> n⩽2 and <?CDATA $\alpha\geqslant 1$?> α⩾1 is arbitrary, or <?CDATA $n\geqslant 1$?> n⩾1 and <?CDATA $\alpha\in [1,2]$?> α∈[1,2] , additional quantitative information on the deviation of trajectories from the initial data is derived. This is found to imply a lower estimate for the spatial oscillation of the respective first components throughout evolution, and moreover this is seen to entail that each of the uncountably many steady states <?CDATA $(u_\star,0)$?> (u⋆,0) of ( <?CDATA $\star$?> ⋆ ) is stable with respect to a suitably chosen norm topology.
Keywords: Applied Mathematics; General Physics and Astronomy; Mathematical Physics; Statistical and Nonlinear Physics

Nonlinear down-conversion in a single quantum dot - Jonas, B.; Heinze, D.; Schöll, E.; Kallert, P.; Langer, T.; Krehs, S.; Widhalm, A.; Jöns, K. D.; Reuter, D.; Schumacher, S.; Zrenner, Artur (Nature Communications)
Abstract Tailored nanoscale quantum light sources, matching the specific needs of use cases, are crucial building blocks for photonic quantum technologies. Several different approaches to realize solid-state quantum emitters with high performance have been pursued and different concepts for energy tuning have been established. However, the properties of the emitted photons are always defined by the individual quantum emitter and can therefore not be controlled with full flexibility. Here we introduce an all-optical nonlinear method to tailor and control the single photon emission. We demonstrate a laser-controlled down-conversion process from an excited state of a semiconductor quantum three-level system. Based on this concept, we realize energy tuning and polarization control of the single photon emission with a control-laser field. Our results mark an important step towards tailored single photon emission from a photonic quantum system based on quantum optical principles.
Keywords: General Physics and Astronomy; General Biochemistry; Genetics and Molecular Biology; General Chemistry

Giant Photoelasticity of Polaritons for Detection of Coherent Phonons in a Superlattice with Quantum Sensitivity - Kobecki, Michal; Scherbakov, Alexey V.; Kukhtaruk, Serhii M.; Yaremkevich, Dmytro D.; Henksmeier, Tobias; Trapp, Alexander; Reuter, Dirk; Gusev, Vitalyi E.; Akimov, Andrey V.; Bayer, Manfred (Physical Review Letters)
Keywords: General Physics and Astronomy

Efficient Frequency Conversion with Geometric Phase Control in Optical Metasurfaces - Reineke Matsudo, Bernhard; Sain, Basudeb; Carletti, Luca; Zhang, Xue; Gao, Wenlong; Angelis, Costantino; Huang, Lingling; Zentgraf, Thomas (Advanced Science)
Keywords: General Physics and Astronomy; General Engineering; Biochemistry; Genetics and Molecular Biology (miscellaneous); General Materials Science; General Chemical Engineering; Medicine (miscellaneous)

Spin-Orbit Interaction of Light Enabled by Negative Coupling in High-Quality-Factor Optical Metasurfaces - Gao, Wenlong; Sain, Basudeb; Zentgraf, Thomas (Physical Review Applied)
Keywords: General Physics and Astronomy

Simultaneous neutron and X-ray tomography for visualization of graphite electrode degradation in fast-charged lithium-ion batteries - Yusuf, Maha; LaManna, Jacob M.; Paul, Partha P.; Agyeman-Budu, David N.; Cao, Chuntian; Dunlop, Alison R.; Jansen, Andrew N.; Polzin, Bryant J.; Trask, Stephen E.; Tanim, Tanvir R.; Dufek, Eric J.; Thampy, Vivek; et al. (Cell Reports Physical Science)
Keywords: General Physics and Astronomy; General Energy; General Engineering; General Materials Science; General Chemistry

Enhanced corrosion resistance of epoxy-films on ultra-thin SiOx PECVD film coated laser surface melted Al-alloys - Varghese, J.; Vieth, P.; Xie, X.; Grundmeier, Guido (SN Applied Sciences)
Abstract The influence of ultra-thin SiO x plasma deposited films on the corrosion resistance of adhesive films on a laser surface melted 7075 aluminium alloy was investigated by means of complementary techniques in comparison to the just laser surface melted state. Laser surface melting (LSM) was performed using a continuous wave mode at a wavelength of 1064 nm. Ultra-thin plasma polymer films were deposited from a mixture of hexamethyldisilane (HMDSO), oxygen, and argon by means of an audio-frequency glow discharge. The surface morphology and surface chemistry compositions were investigated by employing field emission scanning electron microscopy, energy-dispersive X-ray spectroscopy (EDX), diffuse reflection infrared Fourier transform spectroscopy, and X-ray photoelectron spectroscopy. The corrosion resistance of plasma polymer coated LSM Al-7075 alloy was studied using linear sweep voltammetry and electrochemical impedance spectroscopy in a chloride-containing electrolyte. The electrochemical studies showed an improved corrosion resistance for plasma film-coated alloys compared to the just laser surface melted state. To study the corresponding surface adhesive properties, the samples were coated with an epoxy amine adhesive. 90°-peel test under humid conditions confirmed the improvement of interfacial wet-adhesion corrosion tests showed a strong improvement of the delamination resistance of adhesives caused by the ultra-thin interfacial SiO x -films.
Keywords: General Earth and Planetary Sciences; General Physics and Astronomy; General Engineering; General Environmental Science; General Materials Science; General Chemical Engineering

Giant Photoelasticity of Polaritons for Detection of Coherent Phonons in a Superlattice with Quantum Sensitivity - Kobecki, Michal; Scherbakov, Alexey V.; Kukhtaruk, Serhii M.; Yaremkevich, Dmytro D.; Henksmeier, Tobias; Trapp, Alexander; Reuter, Dirk; Gusev, Vitalyi E.; Akimov, Andrey V.; Bayer, Manfred (Physical Review Letters)
Keywords: General Physics and Astronomy

Amplified steady state bifurcations in feedforward networks - von der Gracht, Sören; Nijholt, Eddie; Rink, Bob (Nonlinearity)
We investigate bifurcations in feedforward coupled cell networks. Feedforward structure (the absence of feedback) can be defined by a partial order on the cells. We use this property to study generic one-parameter steady state bifurcations for such networks. Branching solutions and their asymptotics are described in terms of Taylor coefficients of the internal dynamics. They can be determined via an algorithm that only exploits the network structure. Similar to previous results on feedforward chains, we observe amplifications of the growth rates of steady state branches induced by the feedforward structure. However, contrary to these earlier results, as the interaction scenarios can be more complicated in general feedforward networks, different branching patterns and different amplifications can occur for different regions in the space of Taylor coefficients.
Keywords: Applied Mathematics; General Physics and Astronomy; Mathematical Physics; Statistical and Nonlinear Physics

Real-Space Identification of Non-Noble Single Atomic Catalytic Sites within Metal-Coordinated Supramolecular Networks - Schulze Lammers, Bertram; López-Salas, Nieves; Stein Siena, Julya; Mirhosseini, Hossein; Yesilpinar, Damla; Heske, Julian Joachim; Kühne, Thomas; Fuchs, Harald; Antonietti, Markus; Mönig, Harry (ACS Nano)
Keywords: General Physics and Astronomy; General Engineering; General Materials Science

Giant Orbital Anisotropy with Strong Spin–Orbit Coupling Established at the Pseudomorphic Interface of the Co/Pd Superlattice - Kim, Sanghoon; Pathak, Sachin; Rhim, Sonny H.; Cha, Jongin; Jekal, Soyoung; Hong, Soon Cheol; Lee, Hyun Hwi; Park, Sung‐Hun; Lee, Han‐Koo; Park, Jae‐Hoon; Lee, Soogil; Steinrück, Hans-Georg; et al. (Advanced Science)
Keywords: General Physics and Astronomy; General Engineering; Biochemistry; Genetics and Molecular Biology (miscellaneous); General Materials Science; General Chemical Engineering; Medicine (miscellaneous)

Selective area heteroepitaxy of InAs nanostructures on nanopillar-patterned GaAs(111)A - Riedl, Thomas; Kunnathully, Vinay S.; Verma, Akshay Kumar; Langer, Timo; Reuter, Dirk; Büker, Björn; Hütten, Andreas; Lindner, Jörg (Journal of Applied Physics)
A process sequence enabling the large-area fabrication of nanopillar-patterned semiconductor templates for selective-area heteroepitaxy is developed. Herein, the nanopillar tops surrounded by a SiN x mask film serve as nanoscale growth areas. The molecular beam epitaxial growth of InAs on such patterned GaAs[Formula: see text]A templates is investigated by means of electron microscopy. It is found that defect-free nanoscale InAs islands grow selectively on the nanopillar tops at a substrate temperature of 425 °C. High-angle annular dark-field scanning transmission electron microscopy imaging reveals that for a growth temperature of 400 °C, the InAs islands show a tendency to form wurtzite phase arms extending along the lateral [Formula: see text] directions from the central zinc blende region of the islands. This is ascribed to a temporary self-catalyzed vapor–liquid–solid growth on [Formula: see text] B facets, which leads to a kinetically induced preference for the nucleation of the wurtzite phase driven by the local, instantaneous V/III ratio, and to a concomitant reduction of surface energy of the nanoscale diameter arms.
Keywords: General Physics and Astronomy

Nano-FTIR and chemical force analysis of electrografted aryldiazonium salts on ODT-microcontact printed Au-surfaces - Su, Jiangling; González Orive, Alejandro; Grundmeier, Guido (Applied Surface Science)
Keywords: Surfaces; Coatings and Films; Condensed Matter Physics; Surfaces and Interfaces; General Physics and Astronomy; General Chemistry

Nitrous acid in high-pressure oxidation of CH4 doped with nitric oxide: Challenges in the isomer-selective detection and quantification of an elusive intermediate - Hoener, Martin; Kasper, Tina (Combustion and Flame)
Keywords: General Physics and Astronomy; Energy Engineering and Power Technology; Fuel Technology; General Chemical Engineering; General Chemistry

Challenges in the interpretation of gas core levels for the determination of gas-solid interactions within dielectric porous films by ambient pressure XPS - de los Arcos de Pedro, Maria Teresa; Weinberger, Christian; Zysk, Frederik; Raj Damerla, Varun; Kollmann, Sabrina; Vieth, Pascal; Tiemann, Michael; Kühne, Thomas D.; Grundmeier, Guido (Applied Surface Science)
Keywords: Surfaces; Coatings and Films; Condensed Matter Physics; Surfaces and Interfaces; General Physics and Astronomy; General Chemistry

Physics informed neural networks for continuum micromechanics - Henkes, Alexander; Wessels, Henning; Mahnken, Rolf (Computer Methods in Applied Mechanics and Engineering)
Keywords: Computer Science Applications; General Physics and Astronomy; Mechanical Engineering; Mechanics of Materials; Computational Mechanics

Real-Space Identification of Non-Noble Single Atomic Catalytic Sites within Metal-Coordinated Supramolecular Networks - Schulze Lammers, Bertram; Lopez Salas, Nieves; Stein Siena, Julya; Mirhosseini, Hossein; Yesilpinar, Damla; Heske, Julian; Kühne, Thomas D.; Fuchs, Harald; Antonietti, Markus; Mönig, Harry (ACS Nano)
Keywords: General Physics and Astronomy; General Engineering; General Materials Science

Scalable Generation of Multiphoton Entangled States by Active Feed-Forward and Multiplexing - Meyer-Scott, Evan; Prasannan, Nidhin; Dhand, Ish; Eigner, Christof; Quiring, Viktor; Barkhofen, Sonja; Brecht, Benjamin; Plenio, Martin B.; Silberhorn, Christine (Physical Review Letters)
Keywords: General Physics and Astronomy

Scalable Generation of Multiphoton Entangled States by Active Feed-Forward and Multiplexing - Meyer-Scott, Evan; Prasannan, Nidhin; Dhand, Ish; Eigner, Christof; Quiring, Viktor; Barkhofen, Sonja; Brecht, Benjamin; Plenio, Martin B.; Silberhorn, Christine (Physical Review Letters)
Keywords: General Physics and Astronomy

Aluminum Diethylphosphinate as a Flame Retardant for Polyethylene: Investigation of the Pyrolysis and Combustion Behavior of PE/AlPi-Mixtures - Lau, S.; Gonchikzhapov, M.; Paletsky, A.; Shmakov, A.; Korobeinichev, O.; Kasper, Tina; Atakan, B. (Combustion and Flame)
Keywords: General Physics and Astronomy; Energy Engineering and Power Technology; Fuel Technology; General Chemical Engineering; General Chemistry

The role of sulfonate groups and hydrogen bonding in the proton conductivity of two coordination networks - Javed, Ali; Steinke, Felix; Wöhlbrandt, Stephan; Bunzen, Hana; Stock, Norbert; Tiemann, Michael (Beilstein Journal of Nanotechnology)
The proton conductivity of two coordination networks, [Mg(H 2 O) 2 (H 3 L)]·H 2 O and [Pb 2 (HL)]·H 2 O (H 5 L = (H 2 O 3 PCH 2 ) 2 -NCH 2 -C 6 H 4 -SO 3 H), is investigated by AC impedance spectroscopy. Both materials contain the same phosphonato-sulfonate linker molecule, but have clearly different crystal structures, which has a strong effect on proton conductivity. In the Mg-based coordination network, dangling sulfonate groups are part of an extended hydrogen bonding network, facilitating a “proton hopping” with low activation energy; the material shows a moderate proton conductivity. In the Pb-based metal-organic framework, in contrast, no extended hydrogen bonding occurs, as the sulfonate groups coordinate to Pb 2+ , without forming hydrogen bonds; the proton conductivity is much lower in this material.
Keywords: Electrical and Electronic Engineering; General Physics and Astronomy; General Materials Science

Challenges in the interpretation of gas core levels for the determination of gas-solid interactions within dielectric porous films by ambient pressure XPS - de los Arcos, Teresa; Weinberger, Christian; Zysk, Frederik; Raj Damerla, Varun; Kollmann, Sabrina; Vieth, Pascal; Tiemann, Michael; Kühne, Thomas; Grundmeier, Guido (Applied Surface Science)
Near ambient pressure XPS in nitrogen atmosphere was utilized to investigate gas-solid interactions within porous SiO2 films ranging from 30 to 75 nm thickness. The films were differentiated in terms of porosity and roughness. The XPS N1s core levels of the N2 gas in presence of the SiO2 samples showed variations in width, binding energy and line shape. The width correlated with the surface charge induced in the dielectric films upon X-ray irradiation. The observed different binding energies observed for the N1s peak can only partly be associated with intrinsic work function differences between the samples, opening the possibility that the effect of physisorption at room temperature could be detected by a shift in the measured binding energy. However, the signals also show an increasing asymmetry with rising surface charge. This might be associated with the formation of vertical electrical gradients within the dielectric porous thin films, which complicates the assignment of binding energy positions to specific surface-related effects. With the support of Monte Carlo and first principles density functional theory calculations, the observed shifts were discussed in terms of the possible formation of transitory dipoles upon N2 physisorption within the porous SiO2 films.
Keywords: Surfaces; Coatings and Films; Condensed Matter Physics; Surfaces and Interfaces; General Physics and Astronomy; General Chemistry

Steady states of Λ-type three-level systems excited by quantum light with various photon statistics in lossy cavities - Rose, Hendrik; Tikhonova, O V; Meier, Torsten; Sharapova, Polina (New Journal of Physics)
Abstract The interaction between quantum light and matter is being intensively studied for systems that are enclosed in high- Q cavities which strongly enhance the light–matter coupling. Cavities with low Q -factors are generally given less attention due to their high losses that quickly destroy quantum systems. However, bad cavities can be utilized for several applications, where lower Q -factors are required, e.g., to increase the spectral width of the cavity mode. In this work, we demonstrate that low- Q cavities can be beneficial for preparing specific electronic steady states when certain quantum states of light are applied. We investigate the interaction between quantum light with various statistics and matter represented by a Λ-type three-level system in lossy cavities, assuming that cavity losses are the dominant loss mechanism. We show that cavity losses lead to non-trivial electronic steady states that can be controlled by the loss rate and the initial statistics of the quantum fields. We discuss the mechanism of the formation of such steady states on the basis of the equations of motion and present both analytical expressions and numerical simulations for such steady states.
Keywords: General Physics and Astronomy

Nonlinear down-conversion in a single quantum dot - Jonas, B.; Heinze, Dirk Florian; Schöll, E.; Kallert, P.; Langer, T.; Krehs, S.; Widhalm, A.; Jöns, Klaus; Reuter, Dirk; Schumacher, Stefan; Zrenner, Artur (Nature Communications)
Abstract Tailored nanoscale quantum light sources, matching the specific needs of use cases, are crucial building blocks for photonic quantum technologies. Several different approaches to realize solid-state quantum emitters with high performance have been pursued and different concepts for energy tuning have been established. However, the properties of the emitted photons are always defined by the individual quantum emitter and can therefore not be controlled with full flexibility. Here we introduce an all-optical nonlinear method to tailor and control the single photon emission. We demonstrate a laser-controlled down-conversion process from an excited state of a semiconductor quantum three-level system. Based on this concept, we realize energy tuning and polarization control of the single photon emission with a control-laser field. Our results mark an important step towards tailored single photon emission from a photonic quantum system based on quantum optical principles.
Keywords: General Physics and Astronomy; General Biochemistry; Genetics and Molecular Biology; General Chemistry; Multidisciplinary

Helical Polariton Lasing from Topological Valleys in an Organic Crystalline Microcavity - Long, Teng; Ma, Xuekai; Ren, Jiahuan; Li, Feng; Liao, Qing; Schumacher, Stefan; Malpuech, Guillaume; Solnyshkov, Dmitry; Fu, Hongbing (Advanced Science)
Keywords: General Physics and Astronomy; General Engineering; Biochemistry; Genetics and Molecular Biology (miscellaneous); General Materials Science; General Chemical Engineering; Medicine (miscellaneous)

Manipulating polariton condensates by Rashba-Dresselhaus coupling at room temperature - Li, Yao; Ma, Xuekai; Zhai, Xiaokun; Gao, Meini; Dai, Haitao; Schumacher, Stefan; Gao, Tingge (Nature Communications)
Keywords: General Physics and Astronomy; General Biochemistry; Genetics and Molecular Biology; General Chemistry; Multidisciplinary

Bound state solutions of Dirac equation: spin and pseudo-spin symmetry in the presence of the combined Manning–Rosen and Yukawa tensor potentials - Ahmadov, A. I.; Nagiyev, Sh. M.; Aydin, C.; Tarverdiyeva, V. A.; Orujova, M. Sh.; Badalov, S. V. (The European Physical Journal Plus)
Keywords: General Physics and Astronomy; Fluid Flow and Transfer Processes

Direct Measurement of Higher-Order Nonlinear Polarization Squeezing - Prasannan, Nidhin; Sperling, Jan; Brecht, Benjamin; Silberhorn, Christine (Physical Review Letters)
Keywords: General Physics and Astronomy

NTFA-enabled goal-oriented adaptive space–time finite elements for micro-heterogeneous elastoplasticity problems - Ju, X.; Mahnken, Rolf; Xu, Y.; Liang, L. (Computer Methods in Applied Mechanics and Engineering)
Keywords: Computer Science Applications; General Physics and Astronomy; Mechanical Engineering; Mechanics of Materials; Computational Mechanics

New low order Runge–Kutta schemes for asymptotically exact global error estimation of embedded methods without order reduction - Mahnken, Rolf (Computer Methods in Applied Mechanics and Engineering)
Keywords: Computer Science Applications; General Physics and Astronomy; Mechanical Engineering; Mechanics of Materials; Computational Mechanics

Turn all the lights off: Bright- and dark-field second-harmonic microscopy to select contrast mechanisms for ferroelectric domain walls - Hegarty, Peter A.; Beccard, Henrik; Eng, Lukas M.; Rüsing, Michael (Journal of Applied Physics)
Recent analyses by polarization resolved second-harmonic (SH) microscopy have demonstrated that ferroelectric (FE) domain walls (DWs) can possess non-Ising wall characteristics and topological nature. These analyses rely on locally analyzing the properties, directionality, and magnitude of the second-order nonlinear tensor. However, when inspecting FE DWs with SH microscopy, a manifold of different effects may contribute to the observed signal difference between domains and DWs, i.e., far-field interference, Čerenkov-type phase-matching (CSHG), and changes in the aforementioned local nonlinear optical properties. They all might be present at the same time and, therefore, require careful interpretation and separation. In this work, we demonstrate how the particularly strong Čerenkov-type contrast can selectively be blocked using dark- and bright-field SH microscopy. Based on this approach, we show that other contrast mechanisms emerge that were previously overlayed by CSHG but can now be readily selected through the appropriate experimental geometry. Using the methods presented, we show that the strength of the CSHG contrast compared to the other mechanisms is approximately 22 times higher. This work lays the foundation for the in-depth analysis of FE DW topologies by SH microscopy.
Keywords: General Physics and Astronomy

Nonlinear optical interactions in focused beams and nanosized structures - Amber, Zeeshan H.; Spychala, Kai J.; Eng, Lukas M.; Rüsing, Michael (Journal of Applied Physics)
Thin-film materials from μm thickness down to single-atomic-layered 2D materials play a central role in many novel electronic and optical applications. Coherent, nonlinear optical (NLO) μ-spectroscopy offers insight into the local thickness, stacking order, symmetry, or electronic and vibrational properties. Thin films and 2D materials are usually supported on multi-layered substrates leading to (multi-)reflections, interference, or phase jumps at interfaces during μ-spectroscopy, which all can make the interpretation of experiments particularly challenging. The disentanglement of the influence parameters can be achieved via rigorous theoretical analysis. In this work, we compare two self-developed modeling approaches, a semi-analytical and a fully vectorial model, to experiments carried out in thin-film geometry for two archetypal NLO processes, second-harmonic and third-harmonic generation. In particular, we demonstrate that thin-film interference and phase matching do heavily influence the signal strength. Furthermore, we work out key differences between three and four photon processes, such as the role of the Gouy-phase shift and the focal position. Last, we can show that a relatively simple semi-analytical model, despite its limitations, is able to accurately describe experiments at a significantly lower computational cost as compared to a full vectorial modeling. This study lays the groundwork for performing quantitative NLO μ-spectroscopy on thin films and 2D materials, as it identifies and quantifies the impact of the corresponding sample and setup parameters on the NLO signal, in order to distinguish them from genuine material properties.<
Keywords: General Physics and Astronomy

Tuning the Čerenkov second harmonic contrast from ferroelectric domain walls via anomalous dispersion - Hegarty, Peter A.; Eng, Lukas M.; Rüsing, Michael (Journal of Applied Physics)
Second harmonic (SH) microscopy represents a powerful tool for the investigation of crystalline systems, such as ferroelectrics and their domain walls (DWs). Under the condition of normal dispersion, i.e., the refractive index at the SH wavelength is larger as compared to the refractive index at the fundamental wavelength, n(2ω)>n(ω), bulk crystals will generate no SH signal. Should the bulk, however, contain DWs, an appreciable SH signal will still be detectable at the location of DWs stemming from the Čerenkov mechanism. In this work, we demonstrate both how SH signals are generated in bulk media and how the Čerenkov mechanism can be inhibited by using anomalous dispersion, i.e., n(ω)<n(2ω). This allows us to quantitatively estimate the relative strength of the Čerenkov compared to other SH contrast mechanisms in DWs, such as the interference contrast. The results are in agreement with previous experiments based on the geometric separation of the signals. Due to the observed, strong Čerenkov contrast, such signal contributions may not be neglected in polarimetry studies of ferroelectric DWs in the future.
Keywords: General Physics and Astronomy

Threshold photoelectron spectroscopy of trimethylborane and its pyrolysis products - Schleier, Domenik; Gerlach, Marius; Schaffner, Dorothee; Mukhopadhyay, Deb Pratim; Hemberger, Patrick; Fischer, Ingo (Physical Chemistry Chemical Physics)
A new decomposition mechanism for trimethylborane at high temperatures has been discovered.
Keywords: Physical and Theoretical Chemistry; General Physics and Astronomy

Investigation of the combustion chemistry in laminar, low-pressure oxymethylene ether flames (OME0–4) - Gaiser, Nina; Zhang, Hao; Bierkandt, Thomas; Schmitt, Steffen; Zinsmeister, Julia; Kathrotia, Trupti; Hemberger, Patrick; Shaqiri, Shkelqim; Kasper, Tina; Aigner, Manfred; Oßwald, Patrick; Köhler, Markus (Combustion and Flame)
Quantitative speciation data for alternative fuels is highly desired to assess their emission potential and to develop and validate chemical kinetic models. In terms of substitute choices for fossil diesel are oxymethylene ethers (OMEs) strongly discussed. Due to the absence of carbon-carbon bonds, soot emis-sions from combustion of OMEs are low, but significant emissions of unregulated pollutants such as alde-hydes emerge. The combustion behavior of OME fuels with different chain lengths, OME0-4, was investigated in lam-inar premixed low-pressure flames using complementary molecular-beam mass spectrometry (MBMS) techniques. MBMS sampling provides an in-situ access directly into the reaction zone of the flame. Al-most all chemical species involved in the oxidation process can be detected and quantified simultane-ously. Neat OME0-3 flames were analyzed by electron ionization (EI) MBMS with high mass resolution ( R approximate to 3900) providing exact elementary composition. To obtain isomer-specific information, an OME1- doped hydrogen flame and a stochiometric OME4 flame were studied by double-imaging photoelectron photoion coincidence (i2PEPICO) spectroscopy. Both, EI-MBMS detection and i2PEPICO spectroscopy, en-ables a complete overview of all intermediates. The results show a dominance of oxygenated intermediates for all measured conditions. Mole fraction profiles for the most important species are presented (i.e. formaldehyde, methanol, methyl formate and formic acid) and compared to modeling results. Hydrocarbons with more than four carbon atoms were not detected under the investigated conditions. Isomers such as ethanol/dimethyl ether (m/z = 46) and ethenol/acetaldehyde (m/z = 44) could be separated using threshold photoelectron spectra for clear iden-tification and photoionization efficiency curves for quantification. This investigation permits the discus-sion and analysis of systematic trends, including intermediate species, for the combustion of the studied series of oxymethylene ether fuels. (c) 2022 The Combustion Institute. Published by Elsevier Inc. All rights reserved.
Keywords: General Physics and Astronomy; Energy Engineering and Power Technology; Fuel Technology; General Chemical Engineering; General Chemistry

On the diversity of fossil and alternative gasoline combustion chemistry: A comparative flow reactor study - Zinsmeister, Julia; Gaiser, Nina; Melder, Jens; Bierkandt, Thomas; Hemberger, Patrick; Kasper, Tina; Aigner, Manfred; Köhler, Markus; Oßwald, Patrick (Combustion and Flame)
Recent progress in molecular combustion chemistry allows for detailed investigation of the intermediate species pool even for complex chemical fuel compositions, as occur for technical fuels. This study pro-vides detailed investigation of a comprehensive set of complex alternative gasoline fuels obtained from laminar flow reactors equipped with molecular-beam sampling techniques for observation of the com-bustion intermediate species pool in homogeneous gas phase reactions. The combination of ionization techniques including double-imaging photoelectron photoion coincidence (i2PEPICO) spectroscopy enables deeper mechanistic insights into the underlying reaction network relevant to technical fuels. The se-lected fuels focus on contemporary automotive engine application as drop-in fuels compliant to European EN 228 specification for gasoline. Therefore, potential alternative gasoline blends containing oxygenated hydrocarbons as octane improvers obtainable from bio-technological production routes, e.g., ethanol, iso- butanol, methyl tert -butyl ether (MTBE), and ethyl tert -butyl ether (ETBE), as well as a Fischer-Tropsch surrogate were investigated. The fuel set is completed by two synthetic naphtha fractions obtained from Fischer-Tropsch and methanol-to-gasoline processes alongside with a fossil reference gasoline. In total, speciation data for 11 technical fuels from two atmospheric flow reactor setups are presented. Detailed main and intermediate species profiles are provided for slightly rich ( 4) = 1.2) and lean ( 4) = 0.8) con-ditions for intermediate to high temperatures. Complementary, the isomer distribution on different mass channels, like m/z = 78 u fulvene/benzene, of four gasolines was investigated. Experimental findings are analyzed in terms of the detailed fuel composition and literature findings for molecular combustion chemistry. Influences of oxygenated fuel components as well as composition of the hydrocarbon frac-tions are examined with a particular focus on the soot precursor chemistry. This dataset is available for validation of chemical kinetic mechanisms for realistic gasolines containing oxygenated hydrocarbons.(c) 2021 The Combustion Institute. Published by Elsevier Inc. All rights reserved.
Keywords: General Physics and Astronomy; Energy Engineering and Power Technology; Fuel Technology; General Chemical Engineering; General Chemistry

Measurement and modelling solubility of amino acids and peptides in aqueous 2-propanol solutions - Do, Hoang Tam; Franke, Patrick; Volpert, Sophia; Klinksiek, Marcel; Thome, Max; Held, Christoph (Physical Chemistry Chemical Physics)
In this work the solubility of 15 amino acids and 18 peptides in aqueous 2-propanol solutions was successfully modelled using PC-SAFT that used recently determined experimental melting properties as input data.
Keywords: Physical and Theoretical Chemistry; General Physics and Astronomy

Artificial neural networks for the kinetic energy functional of non-interacting fermions - Ghasemi, Alireza; Kühne, Thomas (The Journal of Chemical Physics)
Keywords: Physical and Theoretical Chemistry; General Physics and Astronomy

An automated approach for developing neural network interatomic potentials with FLAME - Mirhosseini, Hossein; Tahmasbi, Hossein; Kuchana, Sai Ram; Ghasemi, Alireza; Kühne, Thomas (Computational Materials Science)
Keywords: Computational Mathematics; General Physics and Astronomy; Mechanics of Materials; General Materials Science; General Chemistry; General Computer Science

The potential and global outlook of integrated photonics for quantum technologies - Pelucchi, Emanuele; Fagas, Giorgos; Aharonovich, Igor; Englund, Dirk; Figueroa, Eden; Gong, Qihuang; Hannes, Hübel; Liu, Jin; Lu, Chao-Yang; Matsuda, Nobuyuki; Pan, Jian-Wei; Schreck, Florian; et al. (Nature Reviews Physics)
Keywords: General Physics and Astronomy

Thermostable water reservoirs in the interlayer space of a sodium hectorite clay through the intercalation of γ-aminopropyl(dimethyl)ethoxysilane in toluene - Keil, Waldemar; Zhao, Kai; Oswald, Arthur; Bremser, Wolfgang; Schmidt, Claudia; Hintze-Bruening, Horst (Physical Chemistry Chemical Physics)
Thermostable compartmentalized sodium-water sites through intercalated γ-aminopropyl-dimethyl-ethoxy silane in synthetic hectorite.
Keywords: Physical and Theoretical Chemistry; General Physics and Astronomy

Low-field onset of Wannier-Stark localization in a polycrystalline hybrid organic inorganic perovskite - Berghoff, Daniel; Bühler, Johannes; Bonn, Mischa; Leitenstorfer, Alfred; Meier, Torsten; Kim, Heejae (Nature Communications)
Abstract Methylammonium lead iodide perovskite (MAPbI 3 ) is renowned for an impressive power conversion efficiency rise and cost-effective fabrication for photovoltaics. In this work, we demonstrate that polycrystalline MAPbI 3 s undergo drastic changes in optical properties at moderate field strengths with an ultrafast response time, via transient Wannier Stark localization. The distinct band structure of this material - the large lattice periodicity, the narrow electronic energy bandwidths, and the coincidence of these two along the same high-symmetry direction – enables relatively weak fields to bring this material into the Wannier Stark regime. Its polycrystalline nature is not detrimental to the optical switching performance of the material, since the least dispersive direction of the band structure dominates the contribution to the optical response, which favors low-cost fabrication. Together with the outstanding photophysical properties of MAPbI 3 , this finding highlights the great potential of this material in ultrafast light modulation and novel photonic applications.
Keywords: General Physics and Astronomy; General Biochemistry; Genetics and Molecular Biology; General Chemistry; Multidisciplinary

Relaxed parameter conditions for chemotactic collapse in logistic-type parabolic–elliptic Keller–Segel systems - Black, Tobias; Fuest, Mario; Lankeit, Johannes (Zeitschrift für angewandte Mathematik und Physik)
Keywords: Applied Mathematics; General Physics and Astronomy; General Mathematics

Prescribed signal concentration on the boundary: Weak solvability in a chemotaxis-Stokes system with proliferation - Black, Tobias; Wu, Chunyan (Zeitschrift für angewandte Mathematik und Physik)
Keywords: Applied Mathematics; General Physics and Astronomy; General Mathematics

Robust ferroelectric polarization retention in harsh environments through engineered domain wall pinning - Zhang, Dawei; Sando, Daniel; Pan, Ying; Sharma, Pankaj; Seidel, Jan (Journal of Applied Physics)
Keywords: General Physics and Astronomy

Diffusion of the carbon dioxide–ethanol mixture in the extended critical region - Chatwell, René Spencer; Guevara-Carrion, Gabriela; Gaponenko, Yuri; Shevtsova, Valentina; Vrabec, Jadran (Physical Chemistry Chemical Physics)
The effect of traces of ethanol in supercritical carbon dioxide on the mixture's thermodynamic properties is studied by molecular simulations and Taylor dispersion measurements.
Keywords: Physical and Theoretical Chemistry; General Physics and Astronomy

Quantifying the coherent interaction length of second-harmonic microscopy in lithium niobate confined nanostructures - Amber, Zeeshan H.; Kirbus, Benjamin; Eng, Lukas M.; Rüsing, Michael (Journal of Applied Physics)
Thin-film lithium niobate (TFLN) in the form of x- or z-cut lithium-niobate-on-insulator has attracted considerable interest as a very promising and novel platform for developing integrated optoelectronic (nano)devices and exploring fundamental research. Here, we investigate the coherent interaction length lc of optical second-harmonic generation (SHG) microscopy in such samples, that are purposely prepared into a wedge shape, in order to elegantly tune the geometrical confinement from bulk thicknesses down to approximately 50 nm. SHG microscopy is a very powerful and non-invasive tool for the investigation of structural properties in the biological and solid-state sciences, especially for visualizing and analyzing ferroelectric domains and domain walls. However, unlike in bulk lithium niobate (LN), SHG microscopy in TFLN is impacted by interfacial reflections and resonant enhancement, both of which rely on film thickness and substrate material. In this paper, we show that the dominant SHG contribution measured on TFLN in backreflection is the co-propagating phase-matched SHG signal and not the counter-propagating SHG portion as is the case for bulk LN samples. Moreover, lc depends on the incident pump laser wavelength (sample dispersion) but also on the numerical aperture of the focussing objective in use. These experimental findings on x- and z-cut TFLN are excellently backed up by our advanced numerical simulations.
Keywords: General Physics and Astronomy

Dimethyl ether (DME) and dimethoxymethane (DMM) as reaction enhancers for methane: Combining flame experiments with model-assisted exploration of a polygeneration process - Zhang, Hao; Kaczmarek, Dennis; Rudolph, Charlotte; Schmitt, Steffen; Gaiser, Nina; Oßwald, Patrick; Bierkandt, Thomas; Kasper, Tina; Atakan, Burak; Kohse-Höinghaus, Katharina (Combustion and Flame)
Keywords: General Physics and Astronomy; Energy Engineering and Power Technology; Fuel Technology; General Chemical Engineering; General Chemistry

In silico investigation of Cu(In,Ga)Se2-based solar cells - Mirhosseini, Hossein; Kormath Madam Raghupathy, Ramya; Sahoo, Sudhir K.; Wiebeler, Hendrik; Chugh, Manjusha; Kühne, Thomas D. (Physical Chemistry Chemical Physics)
State-of-the-art methods in materials science such as artificial intelligence and data-driven techniques advance the investigation of photovoltaic materials.
Keywords: Physical and Theoretical Chemistry; General Physics and Astronomy